Corporate financing of investment opportunities in a world of institutional cross-ownership - Chen, Yangyang; Li, Qingyuan; Ng, Jeffrey; Wang, Chong (Journal of Corporate Finance, 2021)
Institutional cross-owners, specifically institutional investors with significant stakes in multiple firms in the same industry, are becoming increasingly common in the United States. In this paper, we investigate and find that the presence of institutional cross-owners facilitates a firm's financing of its investment opportunities, consistent with institutional cross-owners reducing the adverse selection concerns of those who provide capital for the investment opportunities. We then examine the conditions under which the presence of institutional cross-owners is likely to more significantly reduce adverse selection and thereby have even more of a positive effect on the financing of investment opportunities. We document that relative to transient institutional cross-owners, dedicated institutional cross-owners facilitate more financing of investment opportunities. We also find that institutional cross-owners facilitate the financing of investment opportunities even more for firms with greater dependence on external financing, those with an opaque financial reporting environment, and those with more product market competition. Our paper offers novel insight into how a firm can benefit from the presence of institutional cross-owners.